1994
DOI: 10.1590/s0004-282x1994000200008
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment in human chronic Chagas' disease

Abstract: SUMMARY -We proposed to investigate subclinical cognitive impairment secondary to chronic Chagas' disease (CCD). No similar study was previously done. The neuropsychological performance of 45 chronic Chagasic patients and 26 matched controls (age, education place and years of residency in endemic area) was compared using the Mini Mental State Exam (MMSE), Weschler Memory Scale (WMS) and the Weschler Adult Intelligent Scale (WAIS). Non-parametric tests and Chi2 were used to compare group means and multivariate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
9

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 7 publications
1
25
0
9
Order By: Relevance
“…Therefore, chagasic subjects may also be susceptible to psycho-functional derangements attendant on functional demands for higher cerebral processes in association with their autonomic cardiovascular adaptive disability, as suggested by some evidences 91,92 . In fact, at least in other clinical conditions as the Alzheimer's disease, cognitive status and cardiac autonomic modulation evaluated by heart rate variability appear to be correlated in the sense that people with lower cardiac parasympathetic modulation and tendency for higher sympathetic modulation show more severe cognitive deficiencies 93 .…”
Section: Other Possible Effects Of Autonomic Dysfunctionmentioning
confidence: 99%
“…Therefore, chagasic subjects may also be susceptible to psycho-functional derangements attendant on functional demands for higher cerebral processes in association with their autonomic cardiovascular adaptive disability, as suggested by some evidences 91,92 . In fact, at least in other clinical conditions as the Alzheimer's disease, cognitive status and cardiac autonomic modulation evaluated by heart rate variability appear to be correlated in the sense that people with lower cardiac parasympathetic modulation and tendency for higher sympathetic modulation show more severe cognitive deficiencies 93 .…”
Section: Other Possible Effects Of Autonomic Dysfunctionmentioning
confidence: 99%
“…Com base na referida revisão sistemática, Hueb e Loureiro (2005) identificaram cinco estudos que abordaram os aspectos cognitivos (JORG et al, 1972;MANGONE et al, 1994aMANGONE et al, , 1994bMONCADA et al, 1987;PEREYRA et al, 1992). Tais estudos trataram da inteligência em seus aspectos gerais e específicos, trabalhando com a hipótese de que a doença de Chagas afeta o funcionamento cognitivo dos portadores.…”
Section: Aspectos Cognitivos E Doença De Chagasunclassified
“…Additionally, the various stages of this disease -acute, indeterminate and chronic -make it ideal for studying its covariance with neurocognitive and depressive symptoms. A search through previous literature yielded only one related study: Mangone et al in 1994 suggested that Chagas patients may be impaired in their orientation, attention, nonverbal reasoning, information processing, learning and sequencing 22 . Additionally, according to Oliveira Jr…”
Section: Implications and Conclusionmentioning
confidence: 99%